Cartografía del ser, sentido y significado de la mujer en el pensamiento filosófico de las edades antigua y medieval - Aguilar Gordón, Floralba del Rocío (2020)
The purpose of this paper is to contribute with theoretical-conceptual tools that allow the understanding of the being, sense and meaning of women in the history of ancient and medieval philosophy, reflections that allow understanding the role of women in today's society. A series of alternatives are proposed that lead to the overcoming of the unidirectional thought and the patriarchal character that remain in some sectors and areas of the current society and that has been constructed in a philosophy elaborated by men conceptions that have formed and consolidated a social structure that extends the gap between men and women, granting more power to men. The manuscript reflects the changes experienced by women during the times, in which a historical constant has been the search for freedom, social and political equality of agreement to the circumstances and to the context lived. This manuscript is a bibliographical review that used the deduction as method of investigation, making possible the structure of particular ideas and the comprehension of the reality. Likewise, phenomenological-hermeneutically methods were used to the deepening of the topic object of the investigation, propitiating the analysis and the interpretation of the information.